Case Report: Co-infection of mucormycosis with mycoplasma pneumoniae in children with diabetes mellitus: report of two rare cases - Simijiang, Yipaguli; Abudu, Fawudan; Cui, Yanfei; Abudujielili, Abulikemu (Frontiers in Pediatrics, 2025)
BackgroundMucormycosis is a rare disease characterized by its highly vascular invasiveness, rapid progression, and high mortality rate. Historically, reports on mucormycosis have been concentrated in the adult population, with few cases documented in pediatrics. Notably, there have been no reports of mucormycosis in either adults or children during the prevalence of mycoplasma pneumoniae.Case presentationThis paper presents two cases of newly diagnosed diabetic children who developed concurrent mucormycosis during mycoplasma pneumoniae infection. Both patients received aggressive antifungal therapy, with one surviving and the other succumbing to the disease.ConclusionsThe paper discusses the diagnostic and therapeutic challenges of mucormycosis in patients with diabetes and concurrent mycoplasma pneumoniae, emphasizing the need for more proactive identification of infecting pathogens in the diabetic population during mycoplasma pneumoniae outbreaks. When routine anti-mycoplasma treatments are ineffective and chest enhanced CT scans reveal pulmonary vascular destruction, the possibility of mucormycosis should be considered. Particularly in patients with a history of corticosteroid use, clinical suspicion should be heightened. Concurrent mucormycosis infection may worsen patient outcomes, and further clinical exploration of the pathogenesis and treatment recommendations for mucormycosis associated with mycoplasma pneumoniae is warranted.